1997
DOI: 10.1029/97jd01052
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal variability of summer climate over East Asia and its association with 500 hPa height and global sea surface temperature

Abstract: 19,403

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
171
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(178 citation statements)
references
References 13 publications
5
171
1
1
Order By: Relevance
“…East Asian climate has experienced an interdecadal scale transition near the end of 1970s (Hu, 1997;Wang, 2001;Hu et al, 2003;Han and Wang, 2007). Associated with the inter-decadal climate transition, a strong tropospheric cooling trend is prominent over East Asia during July and August, which contributes to the tendency toward increased droughts in northern China and floods along the Yangtze River valley (often referred to as South China Flood and North China Drought) through changes to the East Asian atmospheric circulation (Yu et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…East Asian climate has experienced an interdecadal scale transition near the end of 1970s (Hu, 1997;Wang, 2001;Hu et al, 2003;Han and Wang, 2007). Associated with the inter-decadal climate transition, a strong tropospheric cooling trend is prominent over East Asia during July and August, which contributes to the tendency toward increased droughts in northern China and floods along the Yangtze River valley (often referred to as South China Flood and North China Drought) through changes to the East Asian atmospheric circulation (Yu et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies suggest that recent warming in the tropical Pacific and India Ocean leads to an abnormal Subtropical Pacific High that reduces water vapor transport to North China from South China Sea and thus contributes to the observed rainfall changes there (Hu 1997;Chang et al 2000;Gong and Ho 2002;Hu et al 2003;Zhou and Huang 2003;Yang and Lau 2004). In particular, Zeng et al (2007), through analyses of model simulations using the National Center for Atmospheric Research (NCAR) community atmospheric model version 3 (CAM3) forced by observed sea surface temperature (SSTs), suggest that the recent warming in the North Indian Ocean and around the South China Sea may have played an important role in the recent EASM weakening.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the East Asian summer monsoon (EASM) has weakened since the late 1970s, which is characterized by the weakening of the 850 hPa southwesterly winds, southward shift of the 200 hPa jet stream, and increases in sea level pressure over East Asia (Hu 1997;Wang 2001;Guo et al 2003;Hu et al 2003;Wang and Ding 2006;Xu et al 2006). Furthermore, a cooling trend in the upper troposphere and lower stratosphere over East Asia has led to the weakening in the northward progression of southerly monsoon winds over this region Yu and Zhou 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The SST is one of the primary variables affected by the initialization. It is known that the western Pacific Ocean influences the interannual and interdecadal variability of East Asian summer monsoon (Huang and Sun, 1992;Hu, 1997). To quantify the relationship between WP SST and the atmospheric circulation in the hindcast, the regression of the zonal and meridional winds at 850 hPa upon the standardized WP SST index are calculated.…”
Section: Sst and Atmospheric Circulationmentioning
confidence: 99%